The Influence of the Digital Era on Corporate Strategic Decisions: A Literature Review - Alfira, Sonya; Anshori, Mochammad; Andriani, Nurita (Jurnal Ilmiah Manajemen Kesatuan, 2023)
The digital age is changing the global landscape through technological innovations such as cloud services, sensors, Big Data analytics and the Internet of Things. These changes affect the global economy and require companies to develop employees to capitalize on opportunities. Employees are becoming important assets in achieving the company's vision, with digital capabilities playing a crucial role in achieving business goals. This article analyzes the impact of the digital age on companies' strategic decisions, focusing on cost efficiency, data collection, and enhanced customer experience. With a qualitative descriptive approach, the article uses narratives to describe the influence of technology in corporate strategy without numerical data. Corporate strategy in the digital age includes staying ahead of the competition, adapting to market changes, developing resources, and achieving financial goals. HR management is also crucial in this adaptation, facing challenges such as integration of new technologies, management of millennial employees, and transformation of HR competencies. Adapting the right strategies, especially those led by corporate objectives, is key to competitive advantage in the digital age, demanding adaptation across various aspects of the business.